Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja terhadap Kinerja Karyawan pada PT Apparel One Indonesia 1 (PT AOI 1) Semarang - Riska Talia Anggoro Weni; Endro Pramono; Teti Safari (Universitas Kristen Indonesia Toraja, 2023)
Every company always wants to achieve its goals while maintaining its existence in society. A company needs humans as implementers to achieve its expectations. Behind the success of a company, it is actually inseparable from the role of leaders who contribute to it. In addition to the role of leaders, employees will be able to carry out their activities well, if supported by good working environment conditions. This study aims to determine and explain the influence of leadership style and work environment on employee performance at PT Apparel One Indonesia 1 Semarang. The object of this study is employees of PT Apparel One Indonesia 1, especially the production department with a total population of 1950 employees and a sample of 95. The data collection technique in this study uses random sampling, where everyone in the target population has an equal opportunity to be selected. The data analysis technique in this study uses multiple linear regression, t-test, f-test, and coefficient of determination test. The research data processing used SPSS version 25. The results of the study can be concluded that: 1. Leadership style has a positive and significant effect on employee performance at PT Apparel One Indonesia 1 Semarang, 2. The work environment has a positive and significant effect on employee performance at PT Apparel One Indonesia 1 Semarang, 3. Leadership style and work environment together have a positive and significant effect on employee performance at PT Apparel One Indonesia 1 Semarang.